Evaluación de la riqueza avifaunística en dos ambientes de la ESPAM MFL como estrategia de conservación de la biodiversidad - Macías Palma, Karen Michelle (2021)
This research aimed to evaluate the Avi faunistic richness of two environments of the ESPAM MFL: CIIDEA and Area 4 of the institution. Non-experimental research was done, where in the first instance a count of birds by points with a distance between points of 200 m and 300 m was carried out. As a result, 40 species and 482 individuals were found in the CIIDEA area as well 40 species were also detected in the area 4 at ESPAM MFL with a total of 486 individuals. More frequently, the Black Thrush (Dives warszewiczi), the Cacique Lomiamarillo (Cacicus cela) and Tortolita Orejuda (Zenaida auroculada) were observed, resulting in an average abundance of 6,305 for both study areas, which is interpreted as an ecosystem of great biodiversity. The value of the Human Disturbance Index (HDI) of each study area was determined, obtaining 66.25% in the CIIDEA area and 42.50% in the area 4 at ESPAM MFL, which validated that the sites closest to the population that exhibited human activities recorded a higher disturbance score; it's considered as a moderate and small impact being the anthropogenic activity that most affects the CIIDEA area soil erosion and for the area 4 the use of agrochemicals. Proposed conservation strategies include maintaining a suitable habitat for bird populations and promoting economic, social and environmental sustainability, which will help control the use of agrochemicals and prevent disturbances to their habitat.